PERSEPSI ATAS KEPEMIMPINAN KEPALA SEKOLAH DAN TINGKAT KESEJAHTERAAN TERHADAP KINERJA GURU - Ahmad Kosasi (Herodotus: Jurnal Pendidikan IPS, 2018)
Thisaim of resorses is for impact knowig perception on leather of head master on weljere teacher to workable teacher. Resources method as useing is survey method resources with double anylisis regression technick. Resources sampling sum 50 (fitty) velue of resources summerise : 1) the influence get as significant perception on head master to ungoverment junior high school in regency of Bekasi. The method improve with : sig. = 0,000 < 0,05 and Fhitung  = 13,135. 2) The influence get as significant perception on head master to ungoverment junior high school in regency of Bekasi. The in fluence get as : sig = 0,00 < 0,05 and thitung = 4,077. 3) The influence get as significant perception on head master to ungoverment junior high school in regency of Bekasi. The in fluence get as : sig = 0,038 < 0,05 and thitung =  2,135. This is illustration resources implication on  1) The influence as direct significant together needs on persaption head master and welfare teacher to workable teacher on ungevermant at regency of Bekasi. This shows as for increasing good workable. Should be doing with re_erase perception on leather of head master 2). The influence The influence as leader head master to teacher workable. This shows as for create workable teacher could be doing for increasing on leader of head master perception. 3). The influence of significant on welfare teacher to workable teacher, this is shows for re_erase workable teacher is needs giving optimal weljere.